The Role of Job Satisfaction in Mediating the Influence of Competence and Emotional Intelligence on the Performance of Paramedics at Bhayangkara Hospital in Bengkulu City - Monika, Wella; Widodo, Slamet (Jurnal Manajemen, 2026)
This study uses job satisfaction as a mediating variable to examine how competence and emotional intelligence affect paramedics’ performance at Bengkulu City’s Bhayangkara Hospital. A saturation sampling strategy was used to choose a sample of 201 respondents for the quantitative study. Questionnaires were used to gather data, and SmartPLS version 3.2 was used for analysis.Nine. According to the study’s findings, paramedic performance is positively and significantly impacted by competence and emotional intelligence, both directly and through job satisfaction. At Bengkulu City’s Bhayangkara Hospital, it has been demonstrated that job satisfaction is a significant mediating element that enhances the impact of competence and emotional intelligence on paramedic performance. This study provides insights for hospital management and policymakers to design more effective human resource management strategies in improving paramedic performance through strengthening competence, emotional intelligence, and job satisfaction.